2019
DOI: 10.1016/j.scitotenv.2018.08.356
|View full text |Cite|
|
Sign up to set email alerts
|

Associations between maternal plasma measurements of inflammatory markers and urinary levels of phenols and parabens during pregnancy: A repeated measures study

Abstract: Background: Maternal immune system regulation is critical for maintenance of a healthy pregnancy and fetal development. Exposure to phenols and parabens is widespread, and may be linked to systemic inflammation and alteration of circulating immunological biomarkers. Objective: We sought to characterize associations between repeated measures of individual urinary phenols, parabens and plasma inflammatory markers across pregnancy. Methods: In the LIFECODES prospective birth cohort, we conducted a nested preterm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 53 publications
(72 reference statements)
0
35
0
Order By: Relevance
“…Therefore, an endocrine-mediated mechanism could potentially be leading to the increase in gestational age. Alternatively, BP-3 was associated with lower concentrations of proinflammatory markers in a large pregnancy cohort (Aung et al, 2019) which may also impact duration of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an endocrine-mediated mechanism could potentially be leading to the increase in gestational age. Alternatively, BP-3 was associated with lower concentrations of proinflammatory markers in a large pregnancy cohort (Aung et al, 2019) which may also impact duration of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…All exposure analytes were measured in urine samples by NSF International in Ann Arbor, MI. Quantification of individual toxicants and analytes followed protocols developed by the Centers for Disease Control and Prevention [44][45][46][47] . We used high-performance liquid chromatography-electrospray ionization tandem mass spectrometry (HPLC-ESI-MS/MS) to quantify a total of nine phthalate metabolites.…”
Section: Methodsmentioning
confidence: 99%
“…The role of these toxic compounds in adverse pregnancy outcome is controversial, as they can have a double effect on the immune system, i.e., a proinflammatory or an anti-inflammatory effect. Aung et al, in 2018, reported that urinary levels of TCS, 2,5-dichlorophenol (2-5-DCP), and MPB in mothers’ urine is associated with an increase of IL-6, IL-12, and TNF alpha, probably through the stimulation of the estrogen receptor, while higher urinary concentrations of EPB and BP3 are associated with lower concentrations of proinflammatory cytokines [68].…”
Section: Resultsmentioning
confidence: 99%